2023
DOI: 10.1029/2022gb007520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Northern Hemisphere Growing Season Net Carbon Flux in Climate Models Using Aircraft Observations

Abstract: Understanding terrestrial ecosystems and their response to anthropogenic climate change requires quantification of land‐atmosphere carbon exchange. However, top‐down and bottom‐up estimates of large‐scale land‐atmosphere fluxes, including the northern extratropical growing season net flux (GSNF), show significant discrepancies. We developed a data‐driven metric for the GSNF using atmospheric carbon dioxide concentration observations collected during the High‐Performance Instrumented Airborne Platform for Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…It has also been used by the global carbon cycle, oceanography, and atmospheric chemistry communities to constrain, often the magnitude and spatial distribution rather than a projection, of greenhouse gas fluxes, ocean heat transports, oxidation rates, ecosystem carbon stocks, etc (e.g., Bian et al, 2023;W. Li et al, 2017;Loechli et al, 2023;Long et al, 2021;Patra et al, 2014;Resplandy et al, 2016;Stephens et al, 2007). Our approach is consistent with this latter group.…”
Section: Methods Overviewsupporting
confidence: 56%
See 1 more Smart Citation
“…It has also been used by the global carbon cycle, oceanography, and atmospheric chemistry communities to constrain, often the magnitude and spatial distribution rather than a projection, of greenhouse gas fluxes, ocean heat transports, oxidation rates, ecosystem carbon stocks, etc (e.g., Bian et al, 2023;W. Li et al, 2017;Loechli et al, 2023;Long et al, 2021;Patra et al, 2014;Resplandy et al, 2016;Stephens et al, 2007). Our approach is consistent with this latter group.…”
Section: Methods Overviewsupporting
confidence: 56%
“…The emergent constraint approach has been widely used in the prognostic climate modeling community to constrain future climate projections based on observations of the current system and emergent relationships from Earth system model ensembles (e.g., Cox, 2019; Hall et al., 2019; Simpson et al., 2021; M. S. Williamson et al., 2021). It has also been used by the global carbon cycle, oceanography, and atmospheric chemistry communities to constrain, often the magnitude and spatial distribution rather than a projection, of greenhouse gas fluxes, ocean heat transports, oxidation rates, ecosystem carbon stocks, etc (e.g., Bian et al., 2023; W. Li et al., 2017; Loechli et al., 2023; Long et al., 2021; Patra et al., 2014; Resplandy et al., 2016; Stephens et al., 2007). Our approach is consistent with this latter group.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent studies have shown dominant impacts of transport uncertainty on our ability to estimate the northern hemisphere land CO 2 sink [13][14][15] . Use of independent observations for validation of inversion estimated CO 2 uxes was promoted in the past decade; however, the regional or semi-hemispheric ux ranges could be narrowed down with limited success over some regions only [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%